SPIRITUALITAS PEMELUK AGAMA ISLAM PADA PENGANUT KEPERCAYAAN KEJAWEN - Agus Abdul Khakam; Hartosujono Hartosujono (JURNAL SPIRITS, 2015)
AbstractThe aims of this reserch is to find out the spiritualism of Moslem who belief Kejawen’s faith. The subject of this research only one person that is a man 52 years old. He works as a spiritualism teacher, his religion is moslem and he believe kejawen faith.This research used qualitative research. The data collection technique of this reserarch are interview and observation. The data analysis techniques consist of three steeps namely,  data reduction, data display, and drawing conclusion.In this research the reseracher found that the subject that moslem religion and adherent of kejawen has high spirituality. It can be seen from his daily activities. He felt happy if he got fairness from God in his life, especially in his prayer. He recognized his identity and his meaning of life. He can recieve all of problems in his life and took the value from the problems. It can be done by combining between Moslem’s pray with Kejawen’s ritual which can create equalization of his life. Key words: spiritualism, Moslem, adherent of Kejawen’s faith